Breast Intra-Ductal Injection of Orexin-A receptor antagonist (SB-334867-A) Decreases Gene Expression of Mammary Lipogenic Enzymes and Insulin Serum Levels in the Lactating rats - Babaei Garmkhani, Sepideh; Khazali, Homayoun (Novelty in Biomedicine, 2022)
Background: Orexins regulate the body’s energy balance during lactation. Also, Orexin A has been reported to have lipogenic effects on adipose tissue, but its role in the mammary glands is unclear. Acetyl CoA carboxylase (ACC) and glucose 6-phosphate dehydrogenase (G6PD) is critical lipogenic enzymes that catalyze the rate-limiting steps in milk fatty acid synthesis. This study was performed for the first time to investigate the effects of blocking the function of orexin-A in lactating female rats on the gene expression of mammary lipogenic enzymes and possible interaction with serum insulin hormone. Materials and Methods: Orexin A receptor antagonist (SB-334867-A) was injected at three doses of 1, 2, and 4 μg/kg BW, in a volume of 50 μl solvent by intra-ductal method into the mammary glands of lactating rats and breast tissues were taken after eight hours. Serum insulin levels using ELISA and the relative expression of mammary ACC and G6PD were measured. Results: Quantitative PCR results showed that by injecting 4 μg/kg BW of SB intra-ductally, a parallel decrease in the gene expression of ACC and G6PD and serum insulin levels was observed compared with the control group. Conclusion: Blocking the function of orexin-A in the lactating rats decreased the expression of lipogenic mammary enzymes and serum insulin.